2021
DOI: 10.1038/s41598-021-95231-z
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating chaotic and stochastic time series using permutation entropy and artificial neural networks

Abstract: Extracting relevant properties of empirical signals generated by nonlinear, stochastic, and high-dimensional systems is a challenge of complex systems research. Open questions are how to differentiate chaotic signals from stochastic ones, and how to quantify nonlinear and/or high-order temporal correlations. Here we propose a new technique to reliably address both problems. Our approach follows two steps: first, we train an artificial neural network (ANN) with flicker (colored) noise to predict the value of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In our methodology, we not only apply dimensionality reduction but also use a fully stochastic "reference" FN time series: we compare the value ofS of the time series of interest with that of a FN time series generated with α = α e . We have shown that the entropy difference, Ω, may provide good contrast for distinguishing fully stochastic time series from a time series with a degree of determinism [9].…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In our methodology, we not only apply dimensionality reduction but also use a fully stochastic "reference" FN time series: we compare the value ofS of the time series of interest with that of a FN time series generated with α = α e . We have shown that the entropy difference, Ω, may provide good contrast for distinguishing fully stochastic time series from a time series with a degree of determinism [9].…”
Section: Introductionmentioning
confidence: 97%
“…We have recently proposed a new method for estimating the strength of the temporal correlations in a given time series, which uses flicker noise (FN), a fully stochastic process, as the reference model [9]. A FN time series, x FN α (t), is characterized by a power spectrum P( f ) ∝ 1/ f α , with α being a parameter that quantifies the temporal correlations present in the signal [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations